Peace, love, & baby ducks - Myracle, Lauren, 1969- (Dutton Books, 2009)
Fifteen-year-old Carly's summer volunteer experience makes her feel more real than her life of privilege in Atlanta ever did, but her younger sister starts high school pretending to be what she is not, and both find their relationships suffering.